Engaging for equity: Lessons from a cross-sector partnership addressing prostate cancer risk in the black community - Tiiu Sildva; Earl Miller; Anthony Henry; Kenneth Noel; Sayeed Ahmed; Sunakshi Chowdhary; Mikaeel Ghany; Heidi Wagner; Yvonne Bombard; Neil Fleshner; Jessica Grace Cockburn (Research Involvement and Engagement)
Plain English summary Black men are more likely to develop earlier and more serious diagnoses of prostate cancer compared to other men. Social and biological factors, such as lifestyle and ancestry, play a large role. Prostate cancer awareness and screening programs in areas with a large black population are important to control risk. Toronto, Ontario has the biggest black community in Canada and is an important place to make sure these programs are effective. A group of community members (doctors, researchers, and patients) from Toronto have come together to learn more about the local community needs and ways to improve awareness and community-based screening. This was the first time team members have worked in this way. This group has selected key lessons from their experiences working together. This includes how to build strong relationships with the local community, the importance of challenging assumptions and unconscious bias, and ways to include people with lived experience (patient partners) in research. These lessons can be a guide for other teams new to health equity work. Through this work, the team as developed creative ways to increase representation in research and assess the needs of Black men in local Toronto communities. Most importantly, these lessons should encourage those hesitant to work in areas leading to advancements in health equity.